Pengelolaan Nilai - Nilai Pendidikan Dalam Permainan Sulap (Sebuah Studi Kasus Pada Solo Magic Community, Komunitas Sulap Kota Solo ) - WIJAYANTI, Neri; , Prof. Dr. Yetty Sardjono, M.Si; , Drs. Ahmad Muhibbin, M.Si (2015)
The study aimed to describe 1). how is the sains education values managements in magic play then describe 2). how is the art education values management in magic played, and the last to describe 3). how is the skill education values management in magic play.The object of this research is magic community in Solo, the name is Solo magic community. Whereas subject of the research is magic play in Solo magic community. The research method in this research is descriptive qualitative. The design of the research is ethnography.The collect data technique in this research with deep interview, observation and documentation.The validation of data in this research with triangulation of source,triangulation of technique and triangulation of time.The result of the research is sains education management,art education management and skill education values management appropriate with management functions in Solo magic community there is planning, organizing, directing and activity evaluation.